INCREASED INCIDENCE OF CUTANEOUS KERATINOCYTIC AND MELANOCYTIC MALIGNANCIES IN PATIENTS WITH AGE-RELATED MACULAR DEGENERATION. Issue 5 (May 2020) - Shah, Saumya M.; Starr, Matthew R.; Dalvin, Lauren A.; Comfere, Nneka I.; AbouChehade, Jackson E.; Hodge, David O.; Iezzi, Raymond; Bakri, Sophie J.
Abstract : Purpose: The relationship between age-related macular degeneration (AMD) and malignancy, especially cutaneous malignancies, is not well studied. We investigated a possible association between AMD and cutaneous malignancies. Methods: A retrospective, consecutive review of all patients who had received at least 1 intravitreal injection for wet AMD between January 1, 2004, and December 31, 2013, was conducted using the Rochester Epidemiology Project in Olmsted County, Minnesota. Age- and sex-matched control groups included 473 pre–anti–vascular endothelial growth factor era wet AMD patients, 504 concurrent time dry AMD patients, and 504 patients with no AMD. The rates of AMD and overall malignancy, cutaneous malignancies, and specific types of cutaneous malignancies were compared between groups of patients. Results: Patients with wet AMD incurred an increased rate of overall malignancies compared to patients with dry AMD 52.8% wet AMD (confidence interval [CI]: 48.3–57.2) vs. 43.7% dry AMD (CI: 39.3–48.1); P = 0.003 or those without AMD (52.8% wet AMD [CI: 48.3–57.2] vs. 35.3% no AMD [CI: 31.1–39.7]; P = <0.001). Patients with dry AMD also had higher rates of malignancy than those without AMD (43.7% dry AMD [CI: 39.3–48.1] vs. 35.3% no AMD [CI: 31.1–39.7]; P = 0.007). Rate of cutaneous malignancies was increased in patients with wet AMD compared to patients with dry AMD (24.4% wet AMD [CI: 20.7–28.4] vs. 14.6% dry AMD [CI: 11.5–17.9]; P = <0.001) and those with no AMD (24.4% wet AMD [CI: 20.7–28.4] vs. 9.7% no AMD [CI: 7.3–12.7]; P = <0.001). Conclusion and Relevance: To the best of our knowledge, this is the first report to establish an association between AMD and cutaneous malignancies, supporting a possible discussion of the association when a patient presents with one of the two conditions. Abstract : In a retrospective study, the rate of cutaneous malignancies was significantly increased in patients with wet and dry age-related macular degeneration. Thus, patients with age-related macular degeneration may be associated with developing cutaneous malignancies and vice versa, supporting a possible change in practice of screening for both conditions upon presentation with either disease.